Ferroptosis: a new dawn in the treatment of acute lymphoblastic leukemia - Han, Jiongping; Yang, Yifan; Wei, Yuxin; Jin, Jing; Feng, Weiying (Frontiers in Oncology, 2026)
Acute lymphoblastic leukemia poses substantial challenges in therapeutic management. As a novel form of programmed cell death, ferroptosis has emerged as a promising research direction in cancer therapy. Studies have emphasized the pivotal role of ferroptosis in ALL, indicating that targeting this pathway could provide a novel therapeutic strategy. This article systematically reviews the molecular regulatory mechanisms of ferroptosis in ALL and explores its potential clinical applications in the treatment and prognostic evaluation of the disease.